Cover Picture: Interrogating the Tailoring Steps of Pactamycin Biosynthesis and Accessing New Pactamycin Analogues (ChemBioChem 17/2016). (19th August 2016) - Abugrain, Mostafa E.; Lu, Wanli; Li, Yuexin; Serrill, Jeffrey D.; Brumsted, Corey J.; Osborn, Andrew R.; Alani, Adam; Ishmael, Jane E.; Kelly, Jane X.; Mahmud, Taifo
Abstract : The cover picture shows the complex biosynthetic pathway to the antitumor antibiotic pactamycin in the soil bacterium Streptomyces pactum . Previous studies have suggested that some of the tailoring enzymes in pactamycin biosynthesis have relaxed substrate specificity that can lead to unspecific modifications of the intermediates. The activity of these promiscuous enzymes not only makes it difficult to determine the actual sequence of the pathway, but also impedes the production of structurally less complex analogues of pactamycin. In this study, a combination of genetic engineering and metabolic analysis was used to gain insights into the natural sequence of events during the tailoring steps of pactamycin biosynthesis and explain the unusual production of various pactamycin analogues by S. pactum mutants. Two new analogues that have better selectivity indices than pactamycin against malarial parasites were also identified. Artist: Seika Mahmud. More information can be found in the communication by T. Mahmud et al. onpage 1585 in Issue 17, 2016 (DOI:10.1002/cbic.201600261 ).